The feasibility of applying three-entry bookkeeping as an approach to enhancing cost control: A case study of Asia Iraq Islamic Bank for Investment and Finance (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aims to investigate the feasibility of implementing three-entry bookkeeping to enhance control over operating expenses at Asia Iraq Islamic Bank for Investment and Finance. The study's significance lies in its potential to improve the accuracy of financial data, enhance transparency and internal control, and reduce financial waste. The study employed a case study methodology and analyzed financial and statistical data. The results demonstrated that three-entry bookkeeping contributed to improved data accuracy and reliability, strengthened internal control, enabled accurate cost analysis by department or project, and supported managerial and digital decision-making. The study recommends the permanent adoption of the system, its integration with digital systems, employee training, the issuance of periodic reports, its expansion to other sectors, and the conduct of periodic reviews to ensure data accuracy and control efficiency.
Keywords: Three-Entry Bookkeeping; Control; Cost Elements; Banks